2013
DOI: 10.3402/edui.v4i1.22064
|View full text |Cite
|
Sign up to set email alerts
|

The politics of intercultural education in Cyprus

Abstract: The main goal of this study is to examine the politics of the development of intercultural education policy in Cyprus. More specifically, it examines the content of intercultural policies developed by the state and particularly the Ministry of Education and Culture. In addition, the study focuses on the challenges that may impede the development and implementation of such policies. The analysis draws upon policy documents collected from the Ministry of Education and Culture and interviews carried out with Cypr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…In other cases, the monocultural approach might be the basis of a relatively absence of AE policies that address migrant learners and migration; giving rise to a policy framework where adult migrant are left to their own devices without serious consideration on ensuring their equal access or promoting their participation in AE and training. There are currently no state-wide policies on AE in Europe that can be termed as entirely monocultural, however, countries such as Denmark and Cyprus are characterised by strong tendencies of monoculturalism (Hajisoteriou & Angelides, 2013; Horst & Thomas Gitz‐Johansen, 2010).…”
Section: European Policies On Ae and Migrationmentioning
confidence: 99%
See 3 more Smart Citations
“…In other cases, the monocultural approach might be the basis of a relatively absence of AE policies that address migrant learners and migration; giving rise to a policy framework where adult migrant are left to their own devices without serious consideration on ensuring their equal access or promoting their participation in AE and training. There are currently no state-wide policies on AE in Europe that can be termed as entirely monocultural, however, countries such as Denmark and Cyprus are characterised by strong tendencies of monoculturalism (Hajisoteriou & Angelides, 2013; Horst & Thomas Gitz‐Johansen, 2010).…”
Section: European Policies On Ae and Migrationmentioning
confidence: 99%
“…As Trimikliniotis and Demetriou (2015) underline, the integration debate has been relatively marginal in Cypriot policies on migration; the term ‘integration’ only began to appear in official policy documents for the first time in 2007. Up to this time, migrants were not even recognised as a group at risk of exclusion due to their temporary residence status (Hajisoteriou & Angelides, 2013, p. 104). The absence of an integration policy framework till the 2010s appears to mirror the failure to develop a coherent migration policy.…”
Section: The Cyprus Case: Political Context and Legal Framework On Migration And Aementioning
confidence: 99%
See 2 more Smart Citations
“…The 'new' policy directive aimed at creating an intercultural school that does not exclude but aims to promote immigrants' inclusion in the educational system and society of Cyprus. Research in the Cypriot context has indicated that although the MEC adopted the rhetoric of intercultural education, its documentation still failed to provide a concrete definition of intercultural education (Hajisoteriou, 2012b;Hajisoteriou & Angelides, 2013). The MEC declared its willingness to promote social justice in education, while eradicating stereotypes and prejudices (MEC, 2008).…”
Section: The Cyprus Context: Education Policy For Intercultural Educamentioning
confidence: 99%